The Foundations of the Human Person’s Dynamism in Karol Wojtyła’s Anthropology. A Study in Light of “The Acting Person” - Duma, Tomasz (Verbum Vitae, 2020)
In traditional anthropology, the problem of the dynamism of the human being was explained by means of human faculties that were seen as distinct from one another on the basis of the activities of man. Having accepted that the traditional approach is well-known and thoroughly elaborated, Karol Wojtyła proposed a complementary approach, enhancing the classical explanation of human dynamism by following the basic intuition of the person who reveals himself in action. In this article, through several steps, the author presents the framework of the basic thesis of Karol Wojtyła’s anthropology, which claims that the action performed by man includes the truth about not only his personal dynamism, but also the very subject of that dynamism itself, that is, the human person. The author shows Wojtyła’s stance beginning with the distinction of personal action made against the background of other forms of human dynamism. Then, he describes Wojtyła’s methods of explanation in reference to the Aristotelian theory of act and potency. Continuing, he analyzes the problem of causativeness of action, which will turn out to be crucial for understanding man as a person. Finally, he sketches Wojtyla’s conception of the fulfillment of man through his action.